2009
DOI: 10.1186/1475-2859-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Altering the ribosomal subunit ratio in yeast maximizes recombinant protein yield

Abstract: Background: The production of high yields of recombinant proteins is an enduring bottleneck in the post-genomic sciences that has yet to be addressed in a truly rational manner. Typically eukaryotic protein production experiments have relied on varying expression construct cassettes such as promoters and tags, or culture process parameters such as pH, temperature and aeration to enhance yields. These approaches require repeated rounds of trial-and-error optimization and cannot provide a mechanistic insight int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
75
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 33 publications
5
75
2
1
Order By: Relevance
“…Subsequent overexpression of BMS1, where the endogenous promoter is replaced with a doxycycline-titratable promoter in the genome, revealed that maximal Fps1 yield was significantly correlated with an optimum level of BMS1 transcript, which was further correlated with a changed ribosomal subunit stoichiometry. This observation was also true at different doxycycline concentrations for hA2aR and soluble GFP [8].…”
Section: The Biosynthesis Of Recombinant Membrane Proteinssupporting
confidence: 62%
See 4 more Smart Citations
“…Subsequent overexpression of BMS1, where the endogenous promoter is replaced with a doxycycline-titratable promoter in the genome, revealed that maximal Fps1 yield was significantly correlated with an optimum level of BMS1 transcript, which was further correlated with a changed ribosomal subunit stoichiometry. This observation was also true at different doxycycline concentrations for hA2aR and soluble GFP [8].…”
Section: The Biosynthesis Of Recombinant Membrane Proteinssupporting
confidence: 62%
“…In our own study of the S. cerevisiae response to membrane protein production [7], genes that were down-regulated under low yielding conditions were up-regulated under high-yielding conditions and vice versa [8] (Table 1). This lent confidence to the fact that these genes might have a role in high-yielding protein production, which was subsequently further validated by strain engineering.…”
Section: The Biosynthesis Of Recombinant Membrane Proteinsmentioning
confidence: 99%
See 3 more Smart Citations